Ius Constituendum of the Regulation for Autonomous Body of Social Organizations in the Security Sector as Reserve Command - Kriswanto Kriswanto (DE LEGA LATA: JURNAL ILMU HUKUM, 2022)
The universal people's defense and security system mandates the importance of the community's role in defense and security efforts against various threats to the Indonesian state. The role of the community in defense and security efforts can be carried out with the participation of the community to become the Reserve Command. In this case, especially for members of the autonomous bodies of community organizations in the security sector, they should have their own space to become the Reserve Command. This research is a juridical-normative legal research with legal issues, namely the legal vacuum in regulating autonomous bodies of social organizations in the security sector to be given a special route to become a member of the reserve component. The approach in this research is the approach to legislation and the concept approach. The results of the study confirm that the urgency to provide special arrangements for members of autonomous community organizations in the security sector to become members of the reserve component because they already have the basics of security skills. In addition, legal construction needs to be carried out by revising the applicable regulations.